Elevating business performance through the use of AIS: the case of Tradepack Industrial Marketing Sdn. Bhd. - Omar, Siti Sarah; Fernandez, Dahlia; Abu Seman, Noor Aslinda (Penerbit UTHM, 2020)
It is not an easy task to capture the performance of businesses without an organized deliberate effort to record and account for the various activities of the business organizations regardless of the sizes and types of business, most particularly the profit-oriented concerns (Ologhodo, et al. 2020). Therefore the use of Accounting Information System (AIS) is inevitable to organizations as to keep up with the change of technology with regard to the accounting related matters. The purpose of the AIS has evolved from the simple use of formal and financial information to incorporate various kinds of information (Chenhall, 2003).